Massive thymic hyperplasia in a toddler masquerading as a loculated pleural effusion: A case report - Emily J. Zolfaghari; Matthew Shaughnessy; Hao Wu; Michael Caty; Emily Christison-Lagay; Matthew A. Hornick (Elsevier, 2024)
Introduction: Pediatric massive thymic hyperplasia is a rare condition that can masquerade as a respiratory illness, making diagnosis challenging. Case presentation: An 18-month-old female with a 3-month history of multiple admissions for suspected pneumonia warranting antibiotics presented with recurrent respiratory distress, fevers, and fatigue. Work-up for possible parapneumonic effusion, including six chest x-rays and an ultrasound, eventually led to a computed tomography (CT) of the chest, which revealed a large homogeneous mass occupying much of the right-hemithorax. Percutaneous core biopsy showed thymocytes suggestive of either a massive thymic hyperplasia or a thymoma. Consensus was to proceed with upfront surgical resection of the mass, which was performed via right thoracotomy. Pathology was consistent with true thymic hyperplasia. The post-operative course was uncomplicated, and no issues were identified at 3-month follow-up. We plan to follow the patient at 6 months, 1 year, and then annually with surveillance chest x-rays to monitor for recurrence case-report. Conclusion: Thymic hyperplasia should be included in the differential diagnosis of pediatric patients with persistent respiratory symptoms and abnormal findings on chest x-ray.